キョクイキ ヒョウショウ シンソウ コア ノ カガク セイブン ブンセキ ヨウ シリョウ ノ オセン ジョキョ マエ ショリ ホウホウ ノ ケントウ - 三宅, 隆之; ミヤケ, タカユキ; 平林, 幹啓; ヒラバヤシ, モトヒロ; 植村, 立; ウエムラ, リュウ; 東, 久美子; アズマ, クミコ; 本山, 秀明; モトヤマ, ヒデアキ; Miyake, Takayuki; Hirabayashi, Motohiro; et al. (情報・システム研究機構国立極地研究所, 2009)
P(論文) 極域氷床深層コアにおける化学成分分析用試料について,イオン成分と固体微小粒子(ダスト)の汚染除去のための前処理方法の検討を行った.超純水でのブランク値がppbレベル以下の清浄なポリ袋と,超純水から作成した模擬コアを用いて,切削および融解による前処理条件を検討した.その結果,当初高濃度の汚染が見られた酢酸を含むイオン成分とダストについて,切削処理により試料外周の約3 mm,融解処理により試料重量の約30%を除去することで,間氷期のドームふじ氷床コアで想定される,イオン濃度で数オg l<-1>以下,ダスト濃度で10000 particles ml<-1> 以下の低濃度試料の分析も対応可能なレベルにまで,汚染を低減できた.以上の検討結果に基づいた,第2期ドームふじ氷床コアの化学成分分析用試料(イオン濃度,ダスト濃度,pH,電気伝導度(EC),水の水素・酸素安定同位体比)の前処理方法についても報告した. We investigated the decontamination procedures used on polar deep ice cores before chemical analyses such as measurements of the concentrations of iron species and dust (microparticles). We optimized cutting and melting protocols for decontamination using chemically ultraclean polyethylene bags and simulated ice samples made from ultrapure water. For dust and ion species including acetate, which represented a high level of contamination, we were able to decrease contamination to below several μg l^<-1> for ion concentrations and below 10000 particles ml^<-1> for the dust concentration. These concentration levels of ion species and dust are assumed to be present in the Dome Fuji ice core during interglacial periods. Decontamination of the ice core was achieved by cutting away approximately 3 mm of the outside of a sample and by melting away approximately 30% of a sample's weight. Furthermore, we also report the preparation protocols for chemical analyses of the 2nd Dome Fuji ice core, including measurements of ion and dust concentrations, pH, electric conductivity (EC), and stable isotope ratios of water (δD and δ<18>O), based on the results of the investigation of the decontamination procedures. departmental bulletin paper